Effect of deep breathing relaxation on pain in postoperative orthopedic patients - Wiki Revi Maqriza; Wigyo Susanto; Betie Febriana (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Postoperative orthopedic pain resulting from surgical trauma and inflammatory response is a major problem commonly experienced by patients. Despite pharmacological therapy, many patients continue to experience moderate to severe pain, necessitating complementary non-pharmacological interventions. Purpose: To determine the effect of the deep breathing relaxation technique in reducing pain intensity among postoperative orthopedic patients. Method: This study employed a quasi-experimental design with a non-equivalent control group. A total of 40 postoperative orthopedic patients participated, selected using total sampling. Pain was assessed using the Verbal Descriptor Scale (VDS). Univariate analysis was used to describe respondents' demographic characteristics, while bivariate analysis was performed using the Wilcoxon signed-rank test. Results: Following the intervention, 80% of the intervention group (n=16) experienced decreased pain intensity, while the control group showed no change. The Wilcoxon signed-rank test revealed a statistically significant difference in pain levels between pre-intervention and post-intervention measurements (p = 0.000). Conclusion: Deep breathing relaxation technique effectively reduces pain intensity in postoperative orthopedic patients. Implementation of this non-pharmacological intervention in routine postoperative care protocols is recommended to enhance multimodal pain management.